The effect of alpha-2 adrenergic receptors on memory retention deficit induced by rapid eye movement sleep deprivation - Norozpour, Yaser (Iran J Basic Med Sci, 2020)
OBJECTIVE(S): Evidence shows that sleep deprivation (SD) disrupts the formation of hippocampus-related memories. Moreover, α2 adrenergic receptors that are wildly expressed in the CA1 hippocampal region have a significant role in modulating both sleep and memory formation. In the present research, we wanted to investigate the effect of stimulation and blockage of CA1 α2 adrenergic receptors by clonidine (an agonist of α2 adrenergic receptor) and yohimbine (an antagonist of α2 adrenergic receptor), respectively, on memory retention impairment induced by REM SD (RSD) in rats. MATERIALS AND METHODS: Multiple platform apparatus were used to induce RSD, and the passive avoidance task was used to assess memory consolidation. Clonidine and yohimbine were injected intra-CA1. RESULTS: The results showed that RSD (for 24 and 36, but not 12 hr) decreased memory retention, with no effect on locomotion. Post-training intra-CA1 infusion of a subthreshold dose of yohimbine (0.001 μg/rat) did not alter, while clonidine (0.1 μg/rat) restored memory retention impairment induced by RSD (24 and 36 hr). Also, none of the interventions did not influence locomotor activity. CONCLUSION: Our data strongly showed that CA1 α2 adrenergic receptors have a critical role in RSD-induced memory retention impairment.